Views of the city from geography, history and urbanism. State of the art at the beginning of XXIst Century (Ciudades, 2017)
In this paper the research on developments that several academic disciplines, especially Geography, have done about the city, since the early twentieth century to the present, is analysed. City is understood as urbs or physical space. This state of the art focuses on the studies conducted by Spanish researchers, which have followed and framed themselves within the predominant paradigms and methods of our scientific and academic environment. That is why the study also refers to epistemological and methodological dynamics of urban studies at the international level, and mainly at the European level.
Keywords: urban geography; urban history; urbanism; city; urban space